Health Counseling and Physical Examination, Blood Pressure, Blood Sugar and Free Treatment at the Hibas Primary Clinic, Simalungun Regency - Purba, Yeni Trisna; Pakpahan, Romauli; Butar-Butar, Doortua; Friani, Sri Rahma; Erhan, Keysha Iszmi; Adelia, Adelia; Wijaya, Imroatulhuda; Abednego, Danuarta Azarya (International Journal of Community Service (IJCS), 2024)
The community service program, "Health education and physical examinations, blood pressure, blood sugar, and free medical treatment at the Pratama Hibas Clinic in Simalungun Regency," was successfully implemented. Health is a human right and an investment for the success of national development. Hypertension, or high blood pressure, is a leading cause of heart failure, stroke, and kidney failure. High blood pressure is called the "silent killer" because people with it often don't show symptoms. The National Heart, Lung, and Blood Institute estimates that half of people with high blood pressure are unaware of their condition. Once diagnosed, patients' blood pressure should be monitored at regular intervals, as high blood pressure is a lifelong condition. Therefore, comprehensive health development is necessary to create a healthy society. The community has received positive feedback, and they hope similar activities will be held regularly. This kind of health education should be ongoing for both the community and their families, as increasing age or apathy among the community can endanger their health. Furthermore, children and siblings in the community also share the responsibility to maintain the health of their fathers, mothers, and siblings with adequate knowledge